Lack of Nationalism in Children: Challenges and Efforts to Strengthen National Identity in the Contemporary Era - Sari, Maya Novita; Asmawati, Asmawati; Jawanti, Ardita Putri Melisa; Syafitri, Desy; Annesta, Dinda; Afandi, Afandi; Dewantara, Jagad Aditya (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
It is very important to teach national identity to children at a young age, especially in the contemporary era where it is difficult to build a national identity. One of the main problems we have is the lack of nationalism among children. This article aims to understand how a child's lack of awareness of nationalism affects the formation of their national identity and how to deal with the challenges of consolidating national identity in the contemporary era. This article was written using qualitative methods using literature studies, including analysis and review of books, journals, articles or other relevant sources. The results of the discussion obtained are the challenges that affect a sense of nationalism in children, the impact of a lack of a sense of nationalism on children, supporting factors for strengthening national identity in children, the role of parents and educators, government initiatives and public policies, and the implications of implementing a sense of nationalism in children . The conclusion is that in this contemporary era there are still many children who lack a sense of nationalism towards their country due to the rapid flow of technology and other environmental influences. To maintain this sense of nationalism, the role of parents, teachers and the government is very much needed in creating a generation of people who love their homeland.